The effects of behind-the-ear and off-the-ear sound processors on speech understanding performance in cochlear implant users - ÇİPRUT, AYŞE AYÇA (ELSEVIER SCI LTD, 2020)
Objective: The first aim of this study was to compare speech understanding performance in adult cochlear implant users using behind-the-ear and off-the-ear sound processors in quiet and noise. Second, the impact of sound processor microphone location on speech understanding performance was compared. Methods: Participants were tested with both types of sound processors in the free field with warble tones, and speech discrimination scores in quiet were obtained. Turkish Matrix Test was used to measure speech understanding in noise with five different loudspeaker settings. Twentyseven participants of cochlear implants between 16 and 67 years-of-age using behind-the-ear or off-the-ear sound processors were included in the study. The results obtained with two types of sound processors were compared. Results: Aided free field thresholds were significantly better for the behind-the-ear vs. off-the ear sound processor. The mean difference was 3.3 dB HL. There was no significant difference in speech discrimination scores in quite between the two processors (p > 0.05). Statistically significant differences were not seen for speech intelligibility in five spatial settings in the Turkish Matrix Test (p > 0.05). Conclusion: Although both types of sound processors had different microphone locations, the outcomes were found to be consistent with previous results in adult users off-the-ear sound processors, demonstrating equivalent speech understanding in quiet and noise. (C) 2020 Oto-Rhino-Laryngological Society of Japan Inc. Published by Elsevier B.V. All rights reserved.
Keywords: Cochlear implant; Speech perception; Sound processor; Behind the ear; Off The Ear; CLINICAL-EVALUATION; BACKGROUND-NOISE; MICROPHONE; PERCEPTION; NUCLEUS; RECOGNITION